2008
DOI: 10.3198/jpr2007.12.0673crc
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘L 79‐1002’ Sugarcane

Abstract: ‘L 79‐1002’ (Reg. No. CV‐132, PI 651501) sugarcane (a complex hybrid of Saccharum officinarum L., S. spontaneum L., S. barberi Jeswiet, and S. sinense Roxb. amend. Jeswiet) was released on 26 Apr. 2007 by the Louisiana State University Agricultural Center in cooperation with the USDA‐ARS and the American Sugarcane League, Inc. The cross for L 79‐1002, a F1 hybrid, was made in 1974 using ‘CP 52‐68’ as the female parent and Tainan, a S. spontaneum clone, as the male parent. Initial clonal selection was done in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 11 publications
7
57
0
4
Order By: Relevance
“…Also, higher S. spontaneum contribution may lead to a rhizomatous habit [57,70], a trait that helps in increasing the resistance of the crown to stresses, mainly the deleterious effect of heavy traffic during harvest and hauling. In conventional sugarcane the yield declines from plant-cane to older ratoons (see review in [67,71]), but some studies have shown that in energy cane it increases from plant cane to first and second ratoons, and high productivity is maintained for at least eight ratoons [24,61,72]. Higher tillering ability has also been observed even in BC 1 clones by several authors as will be mentioned later.…”
Section: Genetic Base and Breeding For Energy Canementioning
confidence: 98%
See 3 more Smart Citations
“…Also, higher S. spontaneum contribution may lead to a rhizomatous habit [57,70], a trait that helps in increasing the resistance of the crown to stresses, mainly the deleterious effect of heavy traffic during harvest and hauling. In conventional sugarcane the yield declines from plant-cane to older ratoons (see review in [67,71]), but some studies have shown that in energy cane it increases from plant cane to first and second ratoons, and high productivity is maintained for at least eight ratoons [24,61,72]. Higher tillering ability has also been observed even in BC 1 clones by several authors as will be mentioned later.…”
Section: Genetic Base and Breeding For Energy Canementioning
confidence: 98%
“…As a result, the Louisiana program succeeded in releasing three cultivars [72,95] and others are coming. In Florida, USA, the breeders also began the breeding of energy canes [38] and Legendre and Burner [37] found that first generation hybrids (F 1 ) are best suited for energy cane pointing out that backcrosses reduce biomass yield components and that the higher the number of backcrosses the higher that dilution.…”
Section: Genetic Base and Breeding For Energy Canementioning
confidence: 99%
See 2 more Smart Citations
“…The idea of using sugarcane as energy plant, rather than just a source of sucrose, was started in the late seventies of past century in the USA because of the oil crisis and the foresight of more problems in the future [55][56][57]. At that time, it was demonstrated that in addition of using sugarcane for the production of fuel ethanol, like Brazil was doing, one could look at the sugarcane as a major biomass producer plant instead of targeting only the stalk and, from this, sucrose only [55].…”
Section: Breeding Energy Cane: the Most Competitive Biomassmentioning
confidence: 99%